Arahan Teknis Pengolahan Limbah Hasil Proses Amalgamasi untuk Menurunkan Kadar Merkuri di Desa Cihonje, Kecamatan Gumelar, Kabupaten Banyumas, Jawa Tengah - Dhimas Mahadhika Putra; Andi Sungkowo; Eni Muryani (Jurnal Ilmiah Lingkungan Kebumian, 2019)
Gold mining activities in Desa Cihonje, Kecamatan Gumelar, Kabupaten Banyumas, Central Java Province still use traditional methods and have not yet treated the wastewater from the amalgamation process, so that there is potential for pollution in the area. There needs to be processing before it is thrown into the environment. The purposes of this study were to analyze and describe the levels of pollution of pH, TSS and mercury (Hg) in waste water and in water bodies, to calculate the effectiveness by using Phytoremediation method with a batch system to reduce pH, TSS and mercury (Hg) and to determine the direction environmental management that can be recommended in the research area.Waste water sampling was based on purposive sampling method. The value of effectiveness is obtained by comparing wastewater with wastewater that has been treated. The experiment was carried out with a laboratory scale for 18 days. To determine the design of the recommended treatment pond, data from the analysis of the effectiveness and environmental conditions are used. Research acquired result for Pij score for river water A1, A2 and A3 are slightly polluted, while Pij score for well water are moderately polluted and for well water 2 are not polluted.  The quality of wastewater from the amalgamation process had TSS content of 5,380 mg/L and mercury of 0.24,482 mg/L. While the results for river water quality contain 110 mg/L, A2 1,812 mg/L and A3 494 mg/L while for mercury A1 0,0001 mg/L, A2 0.02262 mg/L, and 0,02282 mg/L. Groundwater quality for well water 1 contains TSS 66 mg / L and mercury 0.02206 mg/L, while for well water 2 TSS content is 18 mg / L and mercury is 0.00021 mg/L. Phytoremediation method with a batch system has a value of effectiveness for the TSS content of water Eichhornia crassipes by 99.646% and mercury 99.714%. While water Ipomoea aquatica Forsk have a value of effectiveness for TSS content of 99.758% and mercury 99.783% for 18 days.  Keywords:      Amalgamation, Eichhornia crassipes, Ipomoea aquatica Forsk, Phytoremediation